Economic development, carbon emissions and climate policies - Luca Bettarelli; Davide Furceri; Prakash Loungani; Jonathan David Ostry; Loredana Pisano (Bruegel, 2025)
If economic activity is considered the primary driver of climate change through emissions of carbon dioxide, then supporting economic growth and fighting emissions would appear to be at odds. However, the process of economic development may itself foster complementarity between GDP growth and emissions reductions. Such complementary in the relationship between economic development and emissions reduction might reflect changes in the industrial composition of economic activity, technological advancements or environmental consciousness. This view is in line with the Environmental Kuznets Curve (EKC) hypothesis: that per- capita income growth is associated with increases in carbon emissions up to a certain threshold of economic development, but beyond that threshold, higher per-capita incomes are associated with lower emissions per capita. The EKC hypothesis, suggests that economic development is actually a pathway to environmental improvements. We test the EKC hypothesis for 191 countries over 1989-2022, enabling us to study the overall validity of the EKC hypothesis at global level. Moreover, by interacting GDP per capita with an index measuring the stringency of climate policies, we shed light on whether and how climate policies mediate the impact of GDP on emissions. We find that emissions respond to increasing per-capita income levels nonlinearly, with a turning point at about 25,000 on average. Importantly, we show that climate policies shape the relationship between income and emissions by making the EKC lower and flatter, thus favouring a decoupling between emissions and economic activity. Our results have important policy implications, as they identify economic development as a pathway to environmental improvements. We also show that environmental policies are an essential ingredient to achieve decoupling of emissions and economic output over the longer term.
Keywords: C33; Q53; 330; Environmental Kuznets Curve; Climate Change Policy; Decoupling; Carbon Tax